Phacomatosis Pigmentokeratotica - Strano, Serena; Polizzi, Agata; Ruggieri, Martino; Garozzo, Maria Teresa; Mendola, Flavia La; Marino, Simona; Pirrone, Concetta; Zanghì, Antonio; Lacarrubba, Francesco; Micali, Giuseppe; Schepis, Carmelo; Praticò, Elena R.; Praticò, Andrea D. (Journal of Pediatric Neurology, 2018)
In the group of the epidermal nevus syndromes, Happle defined in 1996 a separate entity characterized by the presence of an organoid epidermal nevus, sometimes showing sebaceous differentiation, and a speckled lentiginous nevus of the papular type, occasionally associated with extracutaneous anomalies including neurological, ophthalmological, and skeletal abnormalities. In particular, the syndrome is associated with mental retardation, epilepsy, deafness, hemiatrophy, dysesthesia, and hyperhidrosis, strabismus, lipodermoid of conjunctiva, coloboma and ptosis, and kyphosis, scoliosis, limb asymmetry, and hypertrophy. Rarely, hypertension, vascular abnormalities, atrioventricular block, hypophosphatemic rickets, and pheochromocytoma may occur. The organoid nevus follows the lines of Blaschko whereas the speckled lentiginous nevus is arranged in a checkerboard pattern. For this syndrome, the term “Phacomatosis Pigmentokeratotica” has been coined and, at the present, it is considered a very rare clinical entity, with less than 20 cases reported in the literature. Recent genetic findings have included this syndrome in the group of the mosaic RASopathies, after the discovery of mutations in the HRAS gene occurring in both sebaceous and vascular nevi, but not in nonaffected tissues.
Keywords: epidermal nevi; speckled lentiginous nevus; neurological abnormalities; systemic involvement; limb asymmetry; HRAS gene